The Geothermal Development Policy on Environmental in Indonesia and the USA - Willy Naresta Hanum; I Gusti Ayu Ketut Rachmi Handayani; Hilaire Tegnan (Journal of Human Rights, Culture and Legal System, 2023)
Geothermal utilization is generally used as clean green energy because of its contribution to gradually eliminating high carbon energy. However, in practice, geothermal damage to the environment, even regulation of its utilization does not guarantee environmental justice. This research study aims to determine environmentally just geothermal regulations to eliminate negative environmental impacts and public rejection of geothermal utilization. This study uses normative legal research. The results of this study indicate that geothermal potential can replace high-carbon energy even though it still has a damaging impact on the environment. Community rejection occurs in various areas where geothermal exploitation occurs in conservation forest areas. Geothermal energy regulation in Indonesia is no more pro-ecological than in the USA. Based on the analysis of the legal gap between the theory of ecological justice and the legal triangle and energy policy, it is found that the principles of geothermal regulation must prioritize ecology, not mere exploitation. The findings of this study are strengthening the principles of geothermal regulation based on ecological justice. Standardization of handling and monitoring of environmental impacts must be carried out in an integrated manner based on area category to avoid the widening of the ecological impact of geothermal utilization which results in rejection of the next project.